NETINFERENCE: COMPUTER PROGRAMS FOR REVEALING NETWORK STRUCTURE AND DYNAMICS - I. I. Titov; A. A. Blinov; K. A. Rudnichenko; P. V. Krutov; A. L. Kazantsev; A. I. Kulikov (Вавиловский журнал генетики и селекции)
We present a computer package for analyzing the structure-functional organization and evolution of biological, social and other networks. The programs allows investigation of not only the global network architecture, but also its local properties, revealing key regulators and structure-functional modules. Also, the network evolution can be traced. The package has been tested with two gene networks: the co-authorship network of biomedical papers and the biomedical term network.